The paradox of the long term: human evolution and entanglement. (6th April 2020) - Hodder, Ian
Abstract: Over recent decades, many archaeologists have eschewed evolutionary theories, and in doing so they have turned away from the identification of long‐term trends that are of great relevance to present‐day matters of concern. In particular, there is clear evidence for an overall long‐term increase in the amount of human‐made material and associated human‐thing entanglements, an increase tied up with environmental impact and global inequalities. The directionality of these long‐term changes is clear and yet evolutionary theory largely shuns notions of overall directional change. This paradox and its implications are the subject of this article, with the suggestion made that, for human evolution at least, notions of directionality and path dependence need to be embraced, with concomitant changes in human evolutionary theory, and with implications for responses to environmental change. Adding to earlier accounts of entanglement, emphases are placed on the self‐amplifying processes that lead to change and on irreversibility in the place of teleology. Abstrait: Le paradoxe du long terme : évolution humaine et imbrication Résumé Depuis quelques dizaines d'années, de nombreux archéologues ont tenté d'échapper aux théories de l'évolution et, ce faisant, se sont détournés de l'identification des tendances de longue durée, pourtant très importantes pour les questions qui nous préoccupent aujourd'hui. Les données pointent clairement, en particulier, vers une augmentation globale sur le long terme de la quantité de matière produite par les humains et de son corollaire, l'ensemble des imbrications avec les non‐humains. Cette augmentation est indissociable des impacts environnementaux et des inégalités planétaires. La direction de ces changements au long cours est claire, mais la théorie de l'évolution évite en général les notions de changement dirigé global. Ce paradoxe et ses implications sont le sujet de cet article qui suggère que, dans le cas tout au moins de l'évolution humaine, il importe d'adopter les notions de directionnalité et de « dépendance de sentier » ( path dependence ), en modifiant la théorie de l'évolution humaine et en identifiant les implications pour les réponses aux changements de l'environnement. Venant s'ajouter aux descriptions plus anciennes de cette imbrication, l'auteur met l'accent sur les processus auto‐amplificateurs qui entraînent le changement, et sur l'irréversibilité en lieu et place de la téléologie.